Reasons for violence in school in adolescents perception - Luciana de Lourdes Queiroga Gontijo Netto Maia; Alisson Araújo; Adelino da Silva Santos Júnior (Universidade Federal de Santa Maria, 2012)
Objective: to understand the motivations that lead to the practice of violence in the school context from the perspective of adolescents. Method: we used the qualitative method, and data collected through interviews. The data were evaluated using content analysis. Results: for adolescents, the reasons for school violence were issues related to affective relations between partners, disregard for the physical and social characteristics of the subjects, resistance to the imposition of rules, influence of family structure and drug use. Conclusion: the research shows that the source of violence is multifactorial roots. We stress the need to integrate actions from various sectors in the context of everyday practices of the school, the prospect of building a network capable of providing better care and achieve greater compliance of adolescents, guiding actions to empower them on their access rights services of health promotion